Диферсифікація ринку природного газу ЄС в контексті забезпечення енергетичної безпеки (автореферат) - Музиченко, М.В. (ХНУ імені В. Н. Каразіна, 2018)
Дисертація на здобуття наукового ступеня кандидата економічних наук за спеціальністю 08.00.02 – Світове господарство і міжнародні економічні відносини. – Харківський національний університет імені В.Н. Каразіна Міністерства освіти і науки України, Харків, 2018. Дисертація присвячена поглибленню теоретико-методичних засад дослідження диверсифікації ринку природного газу ЄС та обґрунтуванню перспективних напрямів підвищення енергетичної безпеки ЄС за рахунок диверсифікації ринку газу. У роботі запропоновано енергетичну безпеку трактувати як інтегральну категорію, яка охоплює соціальні, економічні, політичні, технологічні і екологічні фактори і характеризує стан забезпечення економіки енергоресурсами, за якого потреби у енергії задовольняються за стабільними та доступними цінами шляхом використання енергоресурсів з внутрішніх та зовнішніх джерел і стратегічних резервів через надійну та захищену внутрішню енергетичну інфраструктуру і диверсифіковані та стабільно доступні зовнішні джерела, не створюються загрози сталому розвитку та екологічній безпеці і впроваджені механізми мінімізації наявних і потенційних ризиків для енергетичної сфери. У ході дослідження з’ясовано, що в ЄС безпека постачання енергоресурсів визначається як стан забезпечення енергоресурсами, за якого основні енергетичні потреби мають бути задоволені завдяки спільному використанню внутрішніх енергетичних ресурсів та стратегічних резервів у прийнятних економічних умовах та з використанням диверсифікованих та доступних зовнішніх джерел. Проведено аналіз структури та особливостей сучасного ринку газу ЄС і встановлено, що цей ринок займає одне з ключових місць в загальній структурі виробництва первинної енергії в ЄС, а загальним вектором його розвитку є формування єдиного конкурентоспроможного ринку, ключовими елементами якого є вільна конкуренція та біржове ціноутворення на високоліквідних газових хабах. Виявлено, що концепція диверсифікації на основі довгострокових контрактів, яка останнім часом була традиційною в ЄС, на даний час не може повною мірою забезпечити отримання додаткових обсягів імпорту газу. Найбільш привабливою альтернативою є концепція диверсифікації на основі розвитку конкуренції. Запропоновано концептуально-методичний підхід до оцінки рівня диверсифікації ринку газу ЄС на основі індексу диверсифікації ринку, який дозволяє оцінити рівень диверсифікації ринку за основними його аспектами. Удосконалено інструментарій кількісної оцінки рівня диверсифікації зовнішніх джерел постачання, який дозволяє оцінити рівень їх диверсифікації з урахуванням політичної стабільності та економічної доцільності щодо держав-постачальників. Розроблено модель диверсифікації ринку газу, яка дозволяє оцінити як рівень диверсифікації ринку за основними аспектами, так і загальний рівень диверсифікації ринку газу в цілому. Здійснено оцінку рівня диверсифікації ринку газу ЄС і встановлено, що поточний рівень диверсифікації відповідає нормальному рівню диверсифікації. Обґрунтовано перспективні напрями підвищення енергетичної безпеки ЄС за рахунок диверсифікації ринку газу. Визначено пріоритетні шляхи підвищення рівня диверсифікації ринку природного газу України, реалізація комплексу завдань за якими забезпечить задовільний загальний рівень диверсифікації вітчизняного ринку природного газу та є передумовою успішної інтеграції до ринку природного газу ЄС. The thesis for the degree of Candidate of Economic Sciences, speciality 08.00.02 – World Economy and International Economic Relations. – V.N. Karazin Kharkiv National University of the Ministry of Education and Science of Ukraine, Kharkiv, 2018. The thesis is devoted to the in-depth study of the theoretical and methodological research principles of the EU natural gas market diversification as well as to the substantiation of perspectives for the EU energy security increase due to the diversification of gas market. Various approaches to the interpretation of energy security by international organizations, individual countries and academic researchers have been explored in the thesis. It has been established that energy security can be explored either under a one-sided approach based on the security of energy supply or under a multi-faceted approach that takes into account a number of other important aspects of energy security, such as energy availability, energy efficiency and environmental safety. By generalizing the existing approaches to the definition of energy security it has been established that energy security in its broad sense is defined as the state of the Economy energy resources supply, with no threats to sustainable development, and where the mechanisms for compensating existing and potential risks, that may arise as a result of the negative influence of internal or external factors, are implemented. The paper proposes to treat energy security as an integral category that covers social, economic, political, technological and environmental factors and characterizes the state of the economy's energy supply, in which energy needs (in various forms and in sufficient quantities) are met at stable and affordable prices through the use of energy resources from internal and external sources and strategic reserves through a reliable and secure internal energy infrastructure and diversified and stable external energy supply sources, no threat to sustainable development and environmental safety, and mechanisms for minimizing existing and potential risks for the energy sector are introduced. It has been established that central component of the EU energy security is the energy supply security, which means the availability of continuous access to energy resources at affordable prices. The availability of energy resources is a multidimensional concept, the components of which are diversification of energy resources suppliers, spatial diversification of energy resources distribution, diversification of type energy resources and diversification of supply routes (pipelines). The study found that in the EU energy security supply is defined as a state of energy supply, in which the basic energy requirements should be covered through the joint use of internal energy resources and strategic reserves under acceptable economic conditions involving diversified and accessible external sources. Diversification encompasses three aspects: the diversification of supply sources, suppliers, and location of energy objects by spatial criterion. It has been discovered that in order to maintain the appropriate energy security level the energy sector should be characterized by the diversification of the complex of primary energy sources; diversification of electricity production at the expense of gas; diversification of the portfolio of energy resources suppliers; diversification of supply routes for imports; a tendency to reduce the energy intensity of GDP; reliable energy infrastructure; affordable prices. Evaluating the place and role of the diversification in the system of factors of ensuring the EU energy security as one of the largest importers of energy resources in the world, it was established that under the assurance of EU energy security is understood the process of reducing dependence on external energy suppliers through the development of own energy production, diversification of the internal energy portfolio and diversification of the energy resources supply from external sources, the formation of sufficient strategic energy resources reserves, energy efficiency, decarbonisation as a means to combat climate change and minimize pollution. The analysis of the structure and features of the modern EU gas market has proved that this market takes one of the key places in the overall structure of primary energy production in the EU, and its general development trend is the formation of a single competitive market by means of free competition and stock pricing in the most liquid gas hubs. It has been discovered that the concept of diversification on the basis of various longterm contracts can not at this time fully ensure the receipt of additional volumes of gas imports. The most attractive alternative for the coming years is the concept of supply diversification based on the development of competition. The conceptual-methodical approach to assessing the level of diversification of the EU gas market based on the market diversification index is proposed, which allows us to assess the level of market diversification in its main aspects. It is noted that the gas market diversification index is a quantitative measure of how much energy security is ensured in the aspect of diversifying gas supply. The tools for quantifying the level of diversification of external sources of supply have been improved, which allows us to assess the level of their diversification, taking into account political stability and economic expediency. The gas market diversification model is developed, which allows quantitatively and qualitatively to assess both the level of the gas market diversification in its main aspects and the overall level of the gas market diversification as a whole. The assessment of external and internal aspects of the EU gas market diversification has proved that the current level of diversification corresponds to the correct level of diversification according to the proposed scale of assessment. The analysis of the obtained assessments of the EU gas market diversification level has been carried out and promising directions of increasing EU energy security due to natural gas market diversification are provided. The program of diversification of the gas market of Ukraine is proposed on the basis of the analogue of the existing N-1 gas infrastructure standard in the EU. The priority directions of increasing the Ukraine natural gas market diversification level are identified, realization of the tasks complex on which proposed target indicators of Ukraine natural gas market diversification level on the main internal and external aspects inherent in the EU natural gas market, will provide a satisfactory overall level of the domestic natural gas market diversification and is a prerequisite for successful integration with the EU natural gas market. Obtained variants of target values of diversification as target parameters can then be based on the diversification programs and determine the main promising directions of Ukraine natural gas market development in terms of increasing energy efficiency, changing the structure of the energy mix, reduction of natural gas consumption, decreasing the dependence on imports, increasing the diversification level of the external supply sources and suppliers.
Diversification of the EU natural gas market in the context of ensuring energy security
Keywords: енергетична безпека; система забезпечення енергетичної безпеки; ринок газу; диверсифікація постачання енергоресурсів; модель диверсифікації; показник диверсифікації; узагальнений індекс диверсифікації; energy security; energy supply security; energy security system; gas market; energy supply diversification; diversification model; diversification indicator; generalized diversification index